2004
DOI: 10.1007/s00436-004-1193-6
|View full text |Cite
|
Sign up to set email alerts
|

Immune response induced by New World Leishmania species in C57BL/6 mice

Abstract: In the present study, C57BL/6 mice were inoculated with metacyclic Leishmania amazonensis or L. braziliensis promastigotes. While these animals were capable of controlling the infection by L. braziliensis, they developed chronic lesions with elevated numbers of parasites when infected by L. amazonensis. The differences in parasite control were associated with a decreased production of IFN-gamma and TNF by lymph node cells from L. amazonensis-infected mice. Furthermore, these animals presented decreased spleen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
42
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 34 publications
9
42
0
2
Order By: Relevance
“…It was also shown that the CD28/ CD80-CD86 interaction on neutrophil/macrophages induces IFN-␥ production, restricting the growth of L. major (44). Importantly, the mechanisms leading to cure and resistance to Leishmania infection are associated with macrophage activation, resulting from TNF-␣-and IFN-␥-induced production of free radicals and ultimately with destruction of the intracellular parasites (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that the CD28/ CD80-CD86 interaction on neutrophil/macrophages induces IFN-␥ production, restricting the growth of L. major (44). Importantly, the mechanisms leading to cure and resistance to Leishmania infection are associated with macrophage activation, resulting from TNF-␣-and IFN-␥-induced production of free radicals and ultimately with destruction of the intracellular parasites (45,46).…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania infections can result in a wide spectrum of clinical manifestations and disease outcome is determined both by the parasite species and by Correspondence: Dr. Luís C. C. Afonso e-mail: afonso@nupeb.ufop.br the host immune response. Leishmania amazonensis differs from other species because it is able to cause chronic non-healing lesions in mouse strains genuinely resistant to other Leishmania species, such as Leishmania braziliensis and Leishmania major [1][2][3]. In humans, L. amazonensis causes diffuse cutaneous leishmaniasis, a condition characterised by a lack of antigen-specific T-cell responses against the parasite [4].…”
Section: Introductionmentioning
confidence: 99%
“…The GP63, a zinc-metalloprotease named glycoprotein 63 (GP63), is another critical virulence factor that has been fully explored [34][35][36][37][38] . However, the E-NTPDases (ecto-nucleoside triphosphate diphosphohydrolases), while less-extensively studied, have been demonstrated and believed to be important infectivity and virulence factors [39][40][41][42][43][44][45][46][47][48] .…”
Section: Leishmania Braziliensis Is Responsible For Most Cases Of MLmentioning
confidence: 99%